Faktor yang Mempengaruhi Motivasi Guru dalam Menerapkan Kurikulum 2013 di TK ABA Karangkajen Yogyakarta - Maulida, Maulida; Mu'arifah, Alif (Al-Athfal: Jurnal Pendidikan Anak, 2019)
This research is a type of qualitative case study. The subjects in this study were teachers, teacher colleagues, and ABA Karangkajen Kindergarten principals in Yogyakarta. The technique of collecting data uses observation, interviews and documentation. While the instruments used are guidelines for observation, interviews and documentation. Data analysis techniques are data reduction, data display and conclusion drawing / verification. Motivation of teachers in implementing the 2013 curriculum at the ABA Karangkajen Kindergarten in Yogyakarta is influenced by intrinsic and extrinsic factors. The intrinsic factor is like the factor you want to have, self-actualization, love/ affection and religiosity. Extrinsic factors include support from colleagues, parents, principals, and the government in implementing the 2013 curriculum.